Untold Stories of Human Rights Violations in Kashmir - Wani, Hilal Ahmad; Suwirta, Andi; Fayeye, Joseph (EDUCARE, 2013)
ABSTRACT: Kashmir is an intractable conflict between the two South Asian countries: India and Pakistan. It had affected people of tiny nation badly. Every individual suffered here in this vale of paradise which was known as the beautiful region across the globe. But its irony that due to unrest, turmoil, and cycle of violence, people lost their kiths and kens; and because of all that, State of Jammu and Kashmir suffered a lot. This valley has seen plenty of untold stories of massive violations of human rights committed by Indian army, police, and by some of the militant groups. Since 1989, the people of Kashmir were killed, tortured, humiliated, and injured. Thousands of the people were killed due to cycle of violence prevalent in Jammu and Kashmir. Thousands of the people got injuries and they became disabled to work. Many are those who lost their beloved childrenâs, daughters, sisters, mothers, and some women have lost their beloved husbands, who were only the source to care for them. Due to turmoil situations, thousands of the houses and shops were burnt. This study will describe how fundamental rights of the people were encroached and curtailed. It will also highlight how the people of this region were suppressed due to misuse of the armed forces. It is pertinent to mention here that no democracy can be successful where draconian and inhuman laws are prevailing. Democracy can only survive when the dignity of every individual will be respected and safeguarded. Here are tears in every motherâs eyes that lost their beloved children. Everybody here hates violence and is ready to see peaceful Kashmir without any conflict and human rights violations, may this dream of so many become reality.Â  KEY WORDS: Untold stories, violations, fake encounters, draconian laws, psychological disorder and suicides, disappearances in Kashmir, and human rights.Â Â Â Â About the Authors: Dr. Hilal Ahmad Wani is a Post-Doctoral Fellow at the Centre for Peace and Strategic Studies UoI (University of Ilorin) in Ilorin, Nigeria; Andi Suwirta, M.Hum. is a Senior Lecturer at the Faculty of Social Studies Education UPI (Indonesia University of Education) in Bandung; and Dr. Joseph Fayeye is an Associate Professor at the Centre for Peace and Strategic Studies UoI in Ilorin, Nigeria. They can be reached via their e-mail at: wanihilal@gmail.com, andisuwirta@yahoo.com, and josephfayeye@yahoo.comHow to cite this article? Wani, Hilal Ahmad, Andi Suwirta & Joseph Fayeye. (2013). âUntold Stories of Human Rights Violations in Kashmirâ in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.55-68. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 5, 2013); Revised (July 9, 2013); and Published (August 17, 2013).Â Â